Model Pengembangan Kompetensi Penyuluh Berbasis Pemanfaatan Media (Kasus Di Kabupaten Karawang dan Garut, Provinsi Jawa Barat) - E. Oos M. Anwas; Sumardjo Sumardjo; Pang S Asngari; Prabowo Tjitropranoto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2010)
The present study was to the degree of agricultural extension agents’ competency, the dominant factors influence their competency, and also to formulate the model for developing the competency of agricultural extension agents. The study used explanatory research method on 170 agricultural extension agents who work within paddy farmers area (Karawang) and within vegetable farmers area (Garut). Samples from paddy farmers area were taken by using random sampling technique, while those from vegetable farmers area were taken by using census method. Then a data verification was conducted toward 206 farmers who were the clients of the agricultural extension agents. Data collection was conducted during February to April 2009. Data were analyzed using descriptive technique and path analysis. The result of the study showed that the extent of media utilization and the agricultural extension agents’ competency tended to be at a low level. Several dominant factors influenced their their competences.Keyword: agricultural extension agents, mass media, programmed media, environmental media, competencies